Atitude e intenção de uso em sistemas hedônicos: três estudos sobre motivação intrínseca com jogos digitais - Tomaselli, Fernando Claro (2014)
Until recently, research on IS use had a focus on utilitarian systems in the business environment. The popularization of PCs for home use, and the development of the Internet, changed the way the users' interaction with technology is seen. It is no longer seen merely in a utilitarian way, and started to be oriented to hedonic needs, making the IS research to go beyond boundaries of the firm. Research in the field has given increasing attention to the use of hedonic systems, whose objective is to satisfy needs such as entertainment and fun, rather than instrumental value. One hedonic system is getting increasingly prominent, video games. Digital games are present throughout society. There is a growing adoption, institutionalization and ubiquity of video games in everyday life. The new generation was raised with interactive games, and expects the same type of interaction in others IS. Because they are fun and engaging, several organizations are trying to integrate features of digital games in organizational systems, with the expectation of improving employee's motivation and performance and engage consumers online. In order to analyze the relationship of the user with digital games, three surveys were developed. The first discuss the reasons why the individual engages with the game, setting engagement based on challenge, immersion, and curiosity and the individuals motivations were analyzed considering fun and competition. The second research examines the two most widely used constructs in the field to measure such experience, Flow and Cognitive Absorption. The last research uses the concepts explored in the previous two researches to develop a nomological network to predict behavioral intention of the individual to use digital games. As a result, we have a better idea on the factors that lead to players engaged behavior , with the challenge of mastering the game as the most important one, than fun and competition with other players as the least important. Another contribution is the conclusion that Flow and Cognitive Absorption, two of the main constructs used in SI to measure hedonic experience, are not suitable to measure this experience in video games. Finally there is the proposal of a nomological network in an interactive hedonic system context, allowing new researches to benefit from the created path.